TRANSFORMASI PENDIDIKAN DAN PEMBELAJARAN EKONOMI DI KALANGAN ANGGOTA KSU “Jaya Abadi” DI DESA BENDOSARI KECAMATAN SANANKULON KABUPATEN BLITAR - Dian Afidatur Rufaidah; Agung Haryono (Jurnal Pendidikan Ekonomi (Economic Education Journal), 2015)
This study uses qualitative research with a phenomenological approach (naturalistic). Dig up information about the economic transformation of education and learning among members of the KSU "Jaya Abadi" in the village Bendosari Sanankulon Blitar District of both administrators and members. Respondents in this study is pioneering "KSU Jaya Abadi" and members of "KSU Jaya Abadi". Data collection techniques with interview, observation and documentation. These results indicate that the process of non-formal education coupled with economic education / learning among member economies in the form of the application of the knowledge gained from learning from the experiences of others who developed technically and leads to an increase in the income of farmers.